SYNTHESIS OF 4-HYDROXY-3-(1-HYDROXY-2-(SUBSTITUTEDAMINO)ETHYL)-1-PHENYL/ METHYL QUINOLIN-2(1H)-ONE AS ANTICANCER AGENTS - Bajaj, Prachi; Desai, Shivlingrao Mamle; Dighe, Pearl; Naik, Soniya; Biradar, Bheemanagouda (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â  Â Objective: The current work is concerned with the synthesis of a series of 4-hydroxy-3-(1-hydroxy-2-(substituted amino)ethyl)-1-phenyl/ methylquinolin-2(1H)-one[III-a(1-5)/III-b(1-5)] and evaluation of its in vitro anticancer activity. Methods: The starting material for linomide analogs was synthesized by following literature procedures. The carbonyl group was reduced to hydroxyl group using sodium borohydride, and the methyl group was brominated using bromine in acetic acid. Further bromine was nucleophilically substituted by primary amines. All the synthesized compounds were satisfactorily characterized by infrared, nuclear magnetic resonance, and mass spectral data. The synthesized compounds were tested for in vitro anticancer activity against MDA-MB cell line using the MTT assay method. Results: Among all the synthesized compounds, compound [III-a1;R=C6H5,R1=n-propylamine], [III-b1;R=CH3,R1=n-propylamine], and [III-b2;R=CH3,R1=methylamine] were found to be most cytotoxic with IC50 value=25 Î¼g against the MDA-MB cell line. Conclusion: The results of screening studies concluded that compounds with (C6H5 at C1) and (long chain aliphatic and cyclic amines at C3) position of quinolin-2-one ring showed moderate activity.